Hydrogen embrittlement-resistant 1200 MPa-grade dual-phase steel and preparation method thereof
By adding Mo and Nb elements to 1200MPa grade duplex steel, the (Ti,Mo)C precipitation phase and nano-scale precipitates were formed, which solved the problem of insufficient anti-hydrogen embrittlement performance of duplex steel, and achieved high strength and good anti-hydrogen embrittlement ability.
Patent Information
- Application Number
- CN202510120599.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-25
- Publication Date
- 2025-04-11
AI Technical Summary
How to improve the hydrogen embrittlement resistance of 1200MPa grade duplex steel, especially in the case of high martensite content, the risk of hydrogen-induced delayed fracture is high.
By adding a certain amount of Mo elements to the duplex steel, the (Ti,Mo)C precipitation phase is formed to strengthen the grain boundaries, and a large number of nanoscale precipitates are formed by adding Nb elements, the grains are refined and hydrogen traps are provided, which hinders the diffusion of hydrogen.
It effectively improves the hydrogen embrittlement resistance of duplex steel, reduces the ability of hydrogen to damage materials, meets the requirements of high tensile strength and elongation, and extends the U-bend immersion and fracture time.
Smart Images

Figure CN119800235A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of steel manufacturing, and in particular to a hydrogen embrittlement-resistant 1200MPa grade dual-phase steel and a preparation method thereof. Background Art
[0002] With the development of the automotive industry, lightweight, safe, green and energy-saving vehicles have become new trends in the industry. After the strength of automotive steel is improved, higher lightweight and safety can be achieved through thinning of the plate, while reducing carbon emissions during the use of the car and achieving green and low-carbon development, which has also promoted the gradual improvement of the strength of automotive steel. It is reported that in the FSV project of the International Automotive Steel Alliance, high-strength steel with a strength of more than 1000MPa accounts for more than 50%. Among them, duplex steel is the most mature high-strength steel product, and its forming performance has been widely recognized by users, and its usage accounts for the largest proportion of high-strength steel.
[0003] The microstructure of dual-phase steel is mainly ferrite + martensite dual-phase structure, and the material strength gradually increases with the increase of martensite content. The higher the strength, the higher the martensite content. With the increase of the strength of automobile steel, the probability of hydrogen-induced delayed fracture of steel plate increases significantly. Generally speaking, the higher the martensite content in the steel, the higher the sensitivity of hydrogen-induced delayed fracture. In particular, the hydrogen embrittlement performance of dual-phase steel above 1000MPa is very significant, which poses a great safety hazard to user applications and end consumers. Summary of the invention
[0004] The present application provides a hydrogen embrittlement resistant 1200MPa grade dual-phase steel and a preparation method thereof to solve the following technical problem: how to improve the hydrogen embrittlement resistance of 1200MPa grade dual-phase steel.
[0005] In the first aspect, an embodiment of the present application provides a 1200MPa grade dual-phase steel resistant to hydrogen embrittlement. The chemical composition of the dual-phase steel, measured by mass fraction, includes: C: 0.1%~0.15%, Si: 0.2%~0.6%, Mn: 2.2%~2.6%, P≤0.01%, S≤0.005%, Al: 0.02%~0.05%, Cr: 0.1%~0.6%, Mo: 0.1%~0.4%, Nb: 0.01%~0.04%, Ti: 0.02%~0.05%, and matrix element Fe.
[0006] Optionally, the microstructure of the dual-phase steel includes, by area ratio, ferrite: 30% to 50%, martensite: 40% to 60%, and bainite: 3% to 6%.
[0007] Optionally, the microstructure of the dual-phase steel contains nano-scale Nb precipitate particles, nano-scale Ti precipitate particles and (Ti, Mo)C precipitate phase.
[0008] Optionally, the dual-phase steel meets at least one of the following properties: yield strength of 820MPa to 980MPa, tensile strength ≥1180MPa, and elongation A80 ≥5%.
[0009] Optionally, the U-bend immersion fracture time of the dual-phase steel is ≥300h.
[0010] In a second aspect, an embodiment of the present application provides a method for preparing the hydrogen embrittlement resistant 1200 MPa grade dual-phase steel described in the first aspect, the method comprising:
[0011] Obtaining a casting billet having the chemical composition;
[0012] The ingot is sequentially heated, hot-rolled and coiled to obtain a hot-rolled plate;
[0013] performing surface treatment and cold rolling on the hot-rolled sheet in sequence to obtain a cold-rolled sheet;
[0014] The cold-rolled sheet is subjected to continuous annealing and leveling to obtain hydrogen embrittlement-resistant 1200 MPa grade dual-phase steel.
[0015] Optionally, the heating temperature is 1200° C. to 1250° C., and the heating insulation time is 2 h to 3 h.
[0016] Optionally, the final rolling temperature of the hot rolling is 860°C to 920°C.
[0017] Optionally, the coiling temperature is 550°C to 650°C.
[0018] Optionally, the cold rolling reduction rate is 40% to 60%.
[0019] Optionally, the continuous annealing includes: a heating section, a soaking section, a slow cooling section, a fast cooling section and an over-aging section.
[0020] Optionally, the temperature of the heating section is 760° C. to 840° C., and the heating rate of the heating section is 5° C. / s to 10° C. / s.
[0021] Optionally, the duration of the soaking period is 80s to 150s.
[0022] Optionally, the temperature of the slow cooling section is 650°C to 750°C, and the cooling rate of the slow cooling section is 10°C / s to 20°C / s.
[0023] Optionally, the temperature of the rapid cooling section is 300°C to 400°C, and the cooling rate of the rapid cooling section is 20°C / s to 40°C / s.
[0024] Optionally, the time of the over-age period is 500s to 700s.
[0025] Optionally, the flattened elongation is 0.2% to 0.6%.
[0026] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0027] The embodiment of the present application provides a 1200MPa grade dual-phase steel resistant to hydrogen embrittlement. The chemical composition of the dual-phase steel includes, by mass fraction, C: 0.1% to 0.15%, Si: 0.2% to 0.6%, Mn: 2.2% to 2.6%, P≤0.01%, S≤0.005%, Al: 0.02% to 0.05%, Cr: 0.1% to 0.6%, Mo: 0.1% to 0.4%, Nb: 0.01% to 0.04%, Ti: 0.02% to 0.05%, and matrix element Fe. By adding a certain amount of Mo element, a small amount of (Ti, Mo) C is precipitated at the grain boundary to strengthen the grain boundary, improve the hydrogen diffusion barrier, and reduce the ability of hydrogen to damage the material. A certain amount of Nb element is added to form a large number of nano-scale precipitates, which refines the grains and uniformizes the structure, while providing a large number of hydrogen traps to hinder the diffusion of hydrogen, and finally obtain better resistance to hydrogen embrittlement. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0029] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0030] Figure 1 A schematic flow chart of a method for preparing a hydrogen embrittlement resistant 1200MPa grade dual-phase steel provided in an embodiment of the present application;
[0031] Figure 2 A microstructure photograph of the hydrogen embrittlement resistant 1200MPa grade dual-phase steel provided in Example 1 of the present application;
[0032] Figure 3 A photo of the precipitation phase structure of the hydrogen embrittlement resistant 1200MPa grade dual-phase steel provided in Example 1 of the present application;
[0033] Figure 4 This is a graph showing the immersion test results of the hydrogen embrittlement resistant 1200MPa grade dual-phase steel provided in Example 1 of the present application. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0035] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within the range; for example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range; in addition, whenever a numerical range is indicated in this document, it is meant to include any cited numbers (fractions or integers) within the indicated range.
[0036] In this document, the terms including "including" and "including" mean "including but not limited to". Relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. "And / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone; where A and B can be singular or plural. "At least one" means one or more, and "plurality" means two or more; "at least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items; for example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple. "Parts" such as parts by weight and parts by mass indicate the proportional relationship between the components. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, if the mass ratio of substance A, substance B and substance C is 1:2:3, then substance A, substance B and substance C should correspond to the proportional numbers in the proportional formula in the order of description, that is, the mass of substance A: the mass of substance B: the mass of substance C = 1:2:3.
[0037] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this article can be purchased from the market or prepared by existing methods.
[0038] In the first aspect, an embodiment of the present application provides a 1200MPa grade dual-phase steel resistant to hydrogen embrittlement. The chemical composition of the dual-phase steel, measured by mass fraction, includes: C: 0.1%~0.15%, Si: 0.2%~0.6%, Mn: 2.2%~2.6%, P≤0.01%, S≤0.005%, Al: 0.02%~0.05%, Cr: 0.1%~0.6%, Mo: 0.1%~0.4%, Nb: 0.01%~0.04%, Ti: 0.02%~0.05%, and matrix element Fe.
[0039] The positive effect of limiting the mass fraction of C to 0.1% to 0.15% is that element C, as an important component of high-strength steel, can make the material reach a strength level of 1200MPa. At the same time, it can combine with elements such as Nb and Ti to precipitate nano-scale carbides. The precipitated phase can act as a hydrogen trap to inhibit the diffusion of hydrogen and improve the material's resistance to hydrogen embrittlement. However, too high a mass fraction of C will significantly affect the welding performance of the material. For example, the mass fraction of C can be 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, etc.
[0040] The positive effect of limiting the mass fraction of Si to 0.2% to 0.6% is that elemental Si can expand the two-phase region, while promoting the enrichment of austenite stabilizing elements into austenite and purifying ferrite. However, too high a mass fraction of Si will lead to an increase in red rust defects on the hot-rolled surface and reduce the surface quality of the finished product. For example, the mass fraction of Si can be 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, etc.
[0041] The positive effect of limiting the mass fraction of Mn to 2.2% to 2.6% is that Mn plays a role in solid solution strengthening in steel, and can stabilize austenite and improve the strength of the steel plate after quenching. When the mass fraction of Mn is too low, the stability of the residual austenite is poor. When the mass fraction of Mn is too high, it will hinder the ferrite phase transformation and is easy to segregate, and combine with element S to form MnS inclusions. For example, the mass fraction of Mn can be 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, etc.
[0042] The positive effects of limiting the mass fraction of P to ≤0.01% and the mass fraction of S to ≤0.005% are: P and S are harmful elements in steel. P is easy to segregate at the grain boundary, which seriously damages the plasticity and toughness of the steel plate; S combines with manganese and other substances in steel to form plastic inclusions such as manganese sulfide, which is not conducive to the transverse plasticity and toughness of the steel. Therefore, the mass fractions of P and S should be as low as possible. For example, the mass fraction of P can be 0.001%, 0.003%, 0.005%, 0.007%, 0.009%, 0.010%, etc.; the mass fraction of S can be 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, etc.
[0043] The positive effect of limiting the mass fraction of Al to 0.02% to 0.05% is that Al and Si have similar effects and can promote the enrichment of austenite stabilizing elements into austenite and enhance its stability. Since a high mass fraction of Al will cause non-metallic inclusions in molten steel, resulting in nozzle blockage during casting, and a sufficient amount of element Si has been added, the mass fraction of Al is set at 0.02% to 0.05% in the embodiment of the present application. For example, the mass fraction of Al can be 0.02%, 0.025%, 0.03%, 0.035%, 0.04%, 0.045%, 0.05%, etc.
[0044] The positive effect of limiting the mass fraction of Cr to 0.1% to 0.6% is that Cr can significantly improve the hardenability of steel and ensure the strength of the material. However, too high a mass fraction of Cr will seriously reduce the uniform deformation ability of the material. For example, the mass fraction of Cr can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, etc.
[0045] The positive effect of limiting the mass fraction of Mo to 0.1% to 0.4% is that the role of Mo is mainly to improve the tempering stability of martensite. When combined with the element Cr, it can improve the hardenability of steel. At the same time, it can form (Ti, Mo) C precipitation and refine the grains. However, the element Mo is expensive, so the embodiment of the present application limits the mass fraction of Mo to 0.1% to 0.4%. For example, the mass fraction of Mo can be 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, etc.
[0046] The positive effect of limiting the mass fraction of Nb to 0.01% to 0.04% is that the element Nb can combine with the element C to form NbC precipitation, which can play a precipitation strengthening effect. At the same time, the precipitated phase can act as a hydrogen trap to reduce hydrogen diffusion and improve the resistance to hydrogen embrittlement. For example, the mass fraction of Nb can be 0.01%, 0.02%, 0.03%, 0.04%, etc.
[0047] The positive effect of limiting the mass fraction of Ti to 0.02% to 0.04% is that the effect of Ti is similar to that of Nb. Ti can form a titanium compound precipitate phase with N, C and S. Limiting the mass fraction of Ti in steel to form a Ti(C,N) second phase precipitation can provide a fine grain strengthening effect, form (Ti,Mo)C precipitation, and improve the hydrogen embrittlement resistance of the dual-phase steel. Exemplarily, the mass fraction of Ti can be 0.02%, 0.025%, 0.03%, 0.035%, 0.04%, etc.
[0048] Fe is a matrix element. The specific content / content range of Fe can be obtained by the upper and lower limit formula of the component, that is:
[0049] The sum of the percentages of the contents of each component in a composition should be equal to 100%, and the content ranges of several components should meet the following conditions: the upper limit value of a component + the lower limit value of other components ≤ 100; the lower limit value of a component + the upper limit value of other components ≥ 100.
[0050] In some embodiments, the microstructure of the dual-phase steel includes, by area ratio, ferrite: 30% to 50%, martensite: 40% to 60%, and bainite: 3% to 6%.
[0051] Ferrite can provide the material with deformation ability, but too high ferrite content will lead to insufficient tensile strength of the material, so it is set to 30% to 50%. For example, the area ratio of ferrite can be 30%, 35%, 40%, 45%, 50%, etc.; martensite can provide strength for the material, reaching a strength level of 1200MPa. However, while too high a martensite content causes excessive strength, it reduces the ability to resist hydrogen embrittlement, so it is set to 40% to 60%. For example, the area ratio of martensite can be 40%, 45%, 50%, 55%, 60%, etc.; bainite is inevitably produced during the production process, which is beneficial to improve the yield strength of the material, reduce the hardness difference between ferrite and martensite, and improve the overall forming performance of the material. For example, the area ratio of bainite can be 3%, 4%, 5%, 6%, etc.
[0052] In some embodiments, the microstructure of the dual-phase steel contains nano-sized Nb precipitate particles, nano-sized Ti precipitate particles, and (Ti, Mo)C precipitate phase.
[0053] On the one hand, Nb and Ti precipitates refine the grains, make the organization dispersed, and improve the overall resistance of the material to hydrogen embrittlement. In addition, Nb and Ti precipitates can also act as hydrogen traps to reduce the diffusion of hydrogen and improve the material's resistance to hydrogen embrittlement. Ti and Mo precipitates can strengthen the grain boundaries, increase the hydrogen diffusion barrier, reduce the diffusion of hydrogen, and improve the material's resistance to hydrogen embrittlement.
[0054] In some embodiments, the dual-phase steel satisfies at least one of the following properties: yield strength is 820 MPa to 980 MPa, tensile strength is ≥ 1180 MPa, and elongation A80 is ≥ 5%.
[0055] Dual-phase steel improves elongation and overall forming performance on the basis of meeting strength requirements, and is particularly suitable for the production needs of parts with high drawing forming. Exemplarily, the yield strength of dual-phase steel can be 820MPa, 880MPa, 920MPa, 980MPa, etc.; Exemplarily, the tensile strength of dual-phase steel can be 1180MPa, 1200MPa, 1220MPa, 1240MPa, 1260MPa, 1280MPa, 1300MPa, etc.; Exemplarily, the elongation A80 of dual-phase steel can be 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, etc.
[0056] In some embodiments, the U-bend immersion fracture time of the dual-phase steel is ≥300 h.
[0057] Dual-phase steel has good resistance to hydrogen embrittlement, meets the production of parts with high requirements for hydrogen embrittlement resistance, and meets the requirements for parts safety performance and service life. For example, the U-bend immersion fracture time of dual-phase steel can be 300h, 310h, 320h, 330h, 340h, etc.
[0058] Figure 1 A schematic flow chart of a method for preparing a hydrogen embrittlement-resistant 1200 MPa grade dual-phase steel provided in an embodiment of the present application.
[0059] See also Figure 1 In a second aspect, an embodiment of the present application provides a method for preparing the hydrogen embrittlement resistant 1200 MPa grade dual-phase steel described in the first aspect, the method comprising:
[0060] S1, obtaining a casting billet having the chemical composition;
[0061] First, through appropriate smelting and casting processes, a casting billet with a specific chemical composition is prepared. These chemical compositions are the basis for ensuring that the final dual-phase steel has excellent hydrogen embrittlement resistance and a high strength of 1200MPa.
[0062] S2, sequentially heating, hot rolling and coiling the ingot to obtain a hot-rolled plate;
[0063] The ingot is heated to soften the material and remove internal stress. The heated ingot is rolled in a hot rolling mill to form a hot rolled plate. The hot rolling process helps to further improve the material's structure and performance. The hot rolled plate is coiled by a coiler for subsequent processing and transportation.
[0064] In some embodiments, the heating temperature is 1200° C. to 1250° C., and the heating insulation time is 2 h to 3 h.
[0065] The heating temperature is limited to 1200℃~1250℃, and the heating holding time is 2h~3h, so as to make the composition and structure of the ingot uniform, and make the niobium fully dissolved, while reducing oxidation as much as possible. For example, the heating temperature can be 1200℃, 1210℃, 1220℃, 1230℃, 1240℃, 1250℃, etc.; for example, the heating holding time can be 2h, 2.2h, 2.4h, 2.6h, 2.8h, 3h, etc.
[0066] In some embodiments, the final rolling temperature of the hot rolling is 860°C to 920°C.
[0067] In some embodiments, the coiling temperature is 550°C to 650°C.
[0068] The positive effects of limiting the final rolling temperature to 860℃~920℃ and the coiling temperature to 550℃~650℃ are: the final rolling temperature is in the full austenite zone, the coiling temperature is in the bainite transformation zone, the hot rolled structure obtained is ferrite + bainite structure, and a more uniform structure is obtained during subsequent annealing. Too high or too low coiling temperature will directly affect the structure composition of the material after annealing, especially the proportion of martensite, which will directly affect the mechanical properties and hydrogen embrittlement resistance of the material. Exemplarily, the final rolling temperature can be 860℃, 870℃, 880℃, 890℃, 900℃, 910℃, 920℃, etc.; Exemplarily, the coiling temperature can be 550℃, 570℃, 590℃, 610℃, 630℃, 650℃, etc.
[0069] S3, performing surface treatment and cold rolling on the hot-rolled sheet in sequence to obtain a cold-rolled sheet;
[0070] The hot rolled sheet is surface treated to remove impurities such as oxide scale and oil stains on the surface and improve the surface quality of the sheet. The treated hot rolled sheet is rolled in a cold rolling mill to form a cold rolled sheet. The cold rolling process can significantly improve the hardness and strength of the material.
[0071] In some embodiments, the cold rolling reduction ratio is 40% to 60%.
[0072] For example, the reduction ratio of cold rolling may be 40%, 45%, 50%, 55%, 60%, etc.
[0073] S4, continuously annealing and leveling the cold-rolled sheet to obtain hydrogen embrittlement-resistant 1200 MPa grade dual-phase steel.
[0074] The cold-rolled sheet is continuously annealed and tempered to obtain the final hydrogen embrittlement-resistant 1200MPa grade dual-phase steel. The continuous annealing process is the key link for high-strength dual-phase steel to obtain the final excellent mechanical properties. Its process system mainly consists of heating, insulation, slow cooling, rapid cooling and over-aging stages. By controlling these process parameters, the final performance of high-strength dual-phase steel can be effectively regulated.
[0075] In some embodiments, the continuous annealing includes: a heating section, a soaking section, a slow cooling section, a fast cooling section, and an over-aging section.
[0076] In some embodiments, the temperature of the heating section is 760° C. to 840° C., and the heating rate of the heating section is 5° C. / s to 10° C. / s.
[0077] In some embodiments, the soaking period lasts for 80 s to 150 s.
[0078] The temperature of the heating section is limited to 760°C ~ 840°C, the heating rate of the heating section is 5°C / s ~ 10°C / s, and the time of the soaking section is 80s ~ 150s. The above-mentioned insulation temperature is in the ferrite-austenite two-phase region. If the temperature is too low, the austenite content is insufficient, resulting in insufficient final martensite content and strength. If the temperature is too high, there is more austenite, resulting in more martensite content, which reduces the material's resistance to hydrogen embrittlement. Exemplarily, the temperature of the heating section can be 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, etc.; the heating rate of the heating section can be 5°C / s, 6°C / s, 7°C / s, 8°C / s, 9°C / s, 10°C / s, etc.; the time of the soaking section can be 80s, 90s, 100s, 110s, 120s, 130s, 140s, 150s, etc.
[0079] In some embodiments, the temperature of the slow cooling section is 650° C. to 750° C., and the cooling rate of the slow cooling section is 10° C. / s to 20° C. / s.
[0080] The positive effect of limiting the temperature of the slow cooling section to 650°C to 750°C and the cooling rate to 10°C / s to 20°C / s is that the above slow cooling temperature can promote the formation of oriented epitaxial ferrite, promote the enrichment of austenite stabilizing elements into austenite, and improve the stability of austenite. Exemplarily, the temperature of the slow cooling section can be 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, etc.; the cooling rate can be 10°C / s, 12°C / s, 14°C / s, 16°C / s, 18°C / s, 20°C / s, etc.
[0081] In some embodiments, the temperature of the rapid cooling section is 300° C. to 400° C., and the cooling rate of the rapid cooling section is 20° C. / s to 40° C. / s.
[0082] In some embodiments, the time of the over-aging period is 500s to 700s.
[0083] The positive effect of limiting the temperature of the rapid cooling section to 300℃~400℃, the cooling rate to 20℃ / s~40℃ / s, and the time of the over-aging section to 500s~700s is: tempering the martensite and improving the comprehensive mechanical properties. For example, the temperature of the rapid cooling section can be 300℃, 320℃, 340℃, 360℃, 380℃, 400℃, etc.; the cooling rate of the rapid cooling section can be 20℃ / s, 25℃ / s, 30℃ / s, 35℃ / s, 40℃ / s, etc.; the time of the over-aging section can be 500s, 550s, 600s, 650s, 700s, etc.
[0084] In some embodiments, the flattened elongation is 0.2% to 0.6%.
[0085] The positive effect of limiting the flattening elongation to 0.2% to 0.6% is that flattening is a means to obtain a suitable roughness on the surface of the strip steel. Too small or too large a flattening elongation will make the surface roughness too small or too large, so the flattening elongation is set to 0.2% to 0.6%. The flattening elongation can be 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, etc.
[0086] The composition system material described in the embodiment of the present application is processed by hot rolling, cold rolling and annealing to obtain 1200MPa grade dual-phase steel, which has good resistance to hydrogen embrittlement and can be used for the production of components such as automotive structural parts and reinforcement parts.
[0087] The product prepared by the method for preparing the hydrogen embrittlement resistant 1200MPa grade dual-phase steel is the above-mentioned hydrogen embrittlement resistant 1200MPa grade dual-phase steel. Since the method for preparing the hydrogen embrittlement resistant 1200MPa grade dual-phase steel adopts part or all of the technical solutions of the hydrogen embrittlement resistant 1200MPa grade dual-phase steel embodiment, it at least has all the beneficial effects brought by the technical solutions of the hydrogen embrittlement resistant 1200MPa grade dual-phase steel embodiment, which will not be repeated here one by one.
[0088] The present application is further described below in conjunction with specific examples. The experimental methods in the following examples where specific conditions are not specified are usually measured in accordance with national standards / industry standards; if there are no corresponding national standards / industry standards, they are measured in accordance with common international standards, conventional conditions or conditions recommended by the manufacturer.
[0089] The chemical composition of the ingot is shown in Table 1.
[0090] Table 1 Chemical composition of the ingot (wt%), the balance is Fe and unavoidable impurities
[0091]
[0092]
[0093] Based on the chemical composition of the ingots in the embodiment and the comparative example, this embodiment also provides a method for preparing a hydrogen embrittlement resistant 1200 MPa grade dual-phase steel, comprising the following steps:
[0094] Obtaining a casting billet having the chemical composition;
[0095] The ingot is sequentially heated, hot-rolled and coiled to obtain a hot-rolled plate;
[0096] performing surface treatment and cold rolling on the hot-rolled sheet in sequence to obtain a cold-rolled sheet;
[0097] The cold-rolled sheet is subjected to continuous annealing and tempering to obtain a hydrogen embrittlement-resistant 1200 MPa grade dual-phase steel. The main process parameters are shown in Table 2.
[0098] Table 2 Main process parameters of the embodiments and comparative examples
[0099]
[0100] The products obtained in the above examples were subjected to mechanical property tests, where Rp0.2 represents the stress when the non-proportional elongation of the gauge length of the sample reaches 0.2% of the original gauge length; n90 represents that the sample direction is transverse; and the tensile test standard is GB / T228-2002. At the same time, the product was U-bent and then immersed in a 0.1 mol / L hydrochloric acid solution to observe the fracture. The U-bend immersion test standard is: CSAE 155-2020. The obtained data are shown in Table 3 below.
[0101] Table 3 Mechanical properties and hydrogen embrittlement resistance test results
[0102]
[0103]
[0104] As can be seen from Table 3, the embodiment of the present application has obtained a 1200MPa grade hydrogen embrittlement resistant dual-phase steel with a yield strength of 831MPa to 889MPa, a tensile strength of 1200MPa to 1264MPa, an elongation A80 ≥ 5.8%, and a U-bend immersion fracture time of more than 300h through a specific chemical composition design and process combination. This product improves the elongation and overall forming performance on the basis of meeting the strength requirements, and is particularly suitable for the production needs of parts with high drawing forming.
[0105] In contrast, the strength or hydrogen embrittlement resistance of the products prepared in Comparative Examples 1-3 cannot simultaneously meet the target requirements.
[0106] Attached Figure 2-4 Detailed description:
[0107] Figure 2 The microstructure photograph of the hydrogen embrittlement resistant 1200MPa grade dual-phase steel provided in Example 1 of the present application is as follows: Figure 2 As shown, gray is ferrite structure, white is martensite structure, and black is bainite structure.
[0108] Figure 3 The precipitation phase structure photo of the hydrogen embrittlement resistant 1200MPa grade dual-phase steel provided in Example 1 of the present application is as follows: Figure 3 As shown in Figure 5, the precipitated phase contains a large amount of nano-sized Nb, Ti precipitates and (Ti,Mo)C composite precipitates.
[0109] Figure 4 The immersion test result diagram of the hydrogen embrittlement resistant 1200MPa grade dual-phase steel provided in Example 1 of the present application is as follows: Figure 4 As shown in the figure, the duplex steel did not crack after being immersed in 0.1M hydrochloric acid solution for 300h.
[0110] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0111] The embodiments of the present invention can effectively improve the material's resistance to hydrogen embrittlement through component process design, reduce the risk of hydrogen embrittlement fracture of the material during use, improve the high strengthening level and safety performance of automotive steel, and promote lightweight and green development of the automotive industry.
[0112] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. It will be apparent to those skilled in the art that various modifications to these embodiments are possible, and the general principles defined in the present application can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown in the present application, but will conform to the widest range consistent with the principles and novel features applied for by the present application.
Claims
1. A 1200MPa grade dual-phase steel resistant to hydrogen embrittlement, wherein the chemical composition of the dual-phase steel comprises, by mass fraction: C: 0.1% to 0.15%, Si: 0.2% to 0.6%, Mn: 2.2% to 2.6%, P≤0.01%, S≤0.005%, Al: 0.02% to 0.05%, Cr: 0.1% to 0.6%, Mo: 0.1% to 0.4%, Nb: 0.01% to 0.04%, Ti: 0.02% to 0.05%, and matrix element Fe.
2. The dual-phase steel according to claim 1, characterized in that: Calculated by area ratio, the microstructure of the dual-phase steel includes: ferrite: 30% to 50%, martensite: 40% to 60%, and bainite: 3% to 6%.
3. The dual-phase steel according to claim 1, characterized in that The microstructure of the dual-phase steel contains nano-scale Nb precipitate particles, nano-scale Ti precipitate particles and (Ti, Mo)C precipitate phases.
4. The dual-phase steel according to claim 1, characterized in that The dual-phase steel meets at least one of the following properties: yield strength of 820MPa to 980MPa, tensile strength ≥1180MPa, and elongation A80 ≥5%.
5. The dual-phase steel according to claim 1, characterized in that: The U-bend immersion fracture time of the dual-phase steel is ≥300h.
6. A method for preparing the hydrogen embrittlement resistant 1200 MPa grade dual-phase steel according to any one of claims 1 to 5, the method comprising: Obtaining a casting billet having the chemical composition; The ingot is sequentially heated, hot-rolled and coiled to obtain a hot-rolled plate; performing surface treatment and cold rolling on the hot-rolled sheet in sequence to obtain a cold-rolled sheet; The cold-rolled sheet is subjected to continuous annealing and leveling to obtain hydrogen embrittlement-resistant 1200 MPa grade dual-phase steel.
7. The method according to claim 6, characterized in that The heating temperature is 1200° C. to 1250° C., and the heating insulation time is 2 h to 3 h; and / or, The final rolling temperature of the hot rolling is 860°C to 920°C; and / or, The coiling temperature is 550°C to 650°C.
8. The method according to claim 6, characterized in that The cold rolling reduction ratio is 40% to 60%.
9. The method according to claim 6, characterized in that The continuous annealing includes: a heating section, a soaking section, a slow cooling section, a fast cooling section and an over-aging section; wherein, The temperature of the heating section is 760°C to 840°C, and the heating rate of the heating section is 5°C / s to 10°C / s; and / or, The duration of the soaking period is 80s to 150s; and / or, The temperature of the slow cooling section is 650°C to 750°C, and the cooling rate of the slow cooling section is 10°C / s to 20°C / s; and / or, The temperature of the rapid cooling section is 300°C to 400°C, and the cooling rate of the rapid cooling section is 20°C / s to 40°C / s; and / or, The time of the over-ageing period is 500s to 700s.
10. The method according to claim 6, characterized in that The flattened elongation is 0.2% to 0.6%.
Citation Information
Patent Citations
Tensile strength-1200 MPa cold-rolled complex phase steel and preparation method thereof
CN109778062A
1000 MPa-grade dual-phase steel and preparation method thereof
CN117512451A
Hydrogen induced cracking-resistant cold-rolled hot-dip galvanized ultra-high-strength dual-phase steel and manufacturing method therefor
WO2023241677A1